1999
DOI: 10.1177/014556139907800309
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Nasal Erectile Mucosa as Visualized by Magnetic Resonance Imaging

Abstract: We analyzed the distribution of nasal erectile tissue by reviewing five sets of magnetic resonance imaging scans that were obtainedpre-andpost-decongestion. We found that cavernous tissues were located at three sites: the inferior turbinate, the middle turbinate, and the nasal septum. This study reaffirms the findings of previous studies that were performed with other modalities such as computed tomography scanning and cadaver dissections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 6 publications
4
19
0
1
Order By: Relevance
“…17 In the current study, the inferior and MT on the contralateral to the deviation side was found to be statistically significantly larger than on the ipsilateral side and these findings were similar to those of previous studies. [8][9][10][11] The findings of the current study also showed a negative correlation between SB size and the sizes of the inferior and MT s. Namely, SB size decreased as MT size increased, and SB size decreased as IT size increased and the correlation was statistically significant. These findings suggest that the SB is a dynamic structure as nasal turbinates and it may have as much of a role in nasal resistance as nasal turbinates.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…17 In the current study, the inferior and MT on the contralateral to the deviation side was found to be statistically significantly larger than on the ipsilateral side and these findings were similar to those of previous studies. [8][9][10][11] The findings of the current study also showed a negative correlation between SB size and the sizes of the inferior and MT s. Namely, SB size decreased as MT size increased, and SB size decreased as IT size increased and the correlation was statistically significant. These findings suggest that the SB is a dynamic structure as nasal turbinates and it may have as much of a role in nasal resistance as nasal turbinates.…”
Section: Discussionsupporting
confidence: 72%
“…1 Unilateral IT hypertrophy contralateral to the septal deviation side is a common finding previously described as compensatory hypertrophy. [8][9][10][11] Compensatory hypertrophy of the IT protects nasal mucous membranes from excess airflow, which causes dry and crusty nasal mucosa. 8,9 The aim of this study was to compare the sizes of nasal turbinates and the SB on both sides of deviated nasal septums and to evaluate the correlation between SB size and middle and IT sizes.…”
mentioning
confidence: 99%
“…The nasal tissues can vary in size, due to expansile or erectile tissues. 11,12 This feature is due to the complex microvascular anatomy, consisting of capillaries, arteriovenous anastomoses, capacitance vessels or sinusoids, and postcapillary venules. It is the capacitance vessels or sinusoids that are responsible for the ability of nasal structures to change size by virtue of the amount of blood within them increasing or decreasing by several mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…9 In another study, although the medial mucosa and cross-sectional area of the inferior turbinate on the concave side of the septum were significantly decreased by septoplasty, a significant change in the dimensions of the inferior turbinate was not observed on the convex side of the septum. 11 Therefore, the inferior turbinate may demonstrate a much greater change than the middle turbinate, by expanding and shrinking with the change of air volume in the nose. This result could be related to the location and relative amount of erectile tissue in the nose.…”
Section: Discussionmentioning
confidence: 99%